2′, 3′-Dideoxyuridine triphosphate conjugated to SiO2 nanoparticles: Synthesis and evaluation of antiproliferative activity. Issue 7 (15th April 2018) - Vasilyeva, Svetlana V.; Grin, Inga R.; Chelobanov, Boris P.; Stetsenko, Dmitry A.
Graphical abstract: Highlights: Phosphorylated dideoxyuridine (ddU) with SiO2 nanoparticles conjugate was obtained. The conjugate was shown to be potent killer of MCF7 cells. The data demonstrate remarkable clinical potential of novel SiO2 conjugates. Abstract: A conjugate of triphosphorylated 2′, 3′-dideoxyuridine (ddU) with SiO2 nanoparticles was obtained via the CuAAC click chemistry between a γ-alkynyl ddU triphosphate and azido-modified SiO2 nanoparticles. Assessment of cytotoxicity in human breast adenocarcinoma MCF7 cells demonstrated that ddU triphosphate conjugated to SiO2 nanoparticles exhibited a 50% decrease in cancer cell growth at a concentration of 183 ± 57 µg/mL, which corresponds to 22 ± 7 µM of the parent nucleotide, whereas the parent nucleoside, nucleotide and alkynyl triphosphate precursor do not show any cytotoxicity. The data provide an example of remarkable potential of novel conjugates of SiO2 nanoparticles with phosphorylated nucleoside analogues, even those, which have not been used previously as therapeutics, for application as new anticancer agents.